2012
DOI: 10.1007/s00335-012-9411-5
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits

Abstract: We have developed an association-based approach using classical inbred strains of mice in which we correct for population structure, which is very extensive in mice, using an efficient mixed-model algorithm. Our approach includes inbred parental strains as well as recombinant inbred strains in order to capture loci with effect sizes typical of complex traits in mice (in the range of 5 % of total trait variance). Over the last few years, we have typed the hybrid mouse diversity panel (HMDP) strains for a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 41 publications
3
141
0
Order By: Relevance
“…1D; Ghazalpour et al 2012). The number of strains utilized can be selected based on experimental needs with recent studies using 100 strains to investigate behavioral traits (Park et al 2011), 96 strains to study bone mineral density , and 114 strains phenotyped for metabolic traits .…”
Section: Hybrid Mouse Diversity Panel (Hmdp)mentioning
confidence: 99%
“…1D; Ghazalpour et al 2012). The number of strains utilized can be selected based on experimental needs with recent studies using 100 strains to investigate behavioral traits (Park et al 2011), 96 strains to study bone mineral density , and 114 strains phenotyped for metabolic traits .…”
Section: Hybrid Mouse Diversity Panel (Hmdp)mentioning
confidence: 99%
“…Several recent studies (5)(6)(7)(8)(9)(10) have demonstrated the effectiveness of this strategy. To date, dozens of quantitative trait loci (QTLs) (regions of the genome harboring genetic variation influencing a quantitative trait) affecting BMD have been identified in the mouse (11), and recently the pace of identifying QTL genes has rapidly progressed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, formal proof that a specific variant is responsible for a given trait has proven difficult. Buoyed by the prospects and successes of human association studies, several groups have proposed mouse GWAS (Bennett et al 2010;Ghazalpour et al 2012;Valdar et al 2006;Yalcin et al 2010;Churchill et al 2004;Flint and Eskin 2012;Mott and Flint 2013;Kirby et al 2010). For obvious reasons, mouse models have several advantages over human studies.…”
Section: Introductionmentioning
confidence: 99%
“…The environment can be more carefully controlled, measurements can be replicated in genetically identical animals, and the proportion of the variability explained by genetic variation is increased. Complex traits in mouse strains have been shown to have higher heritability and genetic loci often have stronger effects on the trait compared to humans (Lindblad-Toh et al 2000;Wiltshire et al 2003;Yalcin et al 2004) Furthermore, several recently developed strategies for mouse genetic studies, such as use of the hybrid mouse diversity panel (HMDP), provide much higher resolution for associated loci than traditional approaches to quantitative trait loci (QTL) mapping (Bennett et al 2010;Ghazalpour et al 2012). In genome-wide association studies in humans, the use of metaanalysis is becoming more and more popular because one can virtually collect tens of thousands of individuals that will provide power to identify associated variants with small effect sizes (Hinds et al 2013;Anttila et al 2013;Berndt et al 2013).…”
Section: Introductionmentioning
confidence: 99%